PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PENIPUAN DENGAN MODUS MEMBELI SERTA MENYERAHKAN HANDPHONE KORBAN DI RUMAH ORANG LAIN - BMY, M. Akbar Adjiguna; Hasan, Zainudin (TAHKIM, 2025)
Fraud is a criminal act regulated in the Criminal Code (KUHP) and has serious consequences. However, the challenge they face in law enforcement is the difficulty in collecting strong evidence and identifying fake identities or operating outside the rule of law. Fraud is a crime that has property as its object. In the Criminal Code (KUHP), the crime of fraud is regulated in chapter XXV BOOK II and is contained in Article 378 which reads: Whoever, with the intention of unlawfully benefiting himself or another person, uses a false name or false dignity. who, by deception or a series of lies, induces another person to hand over something to him, or to give a debt or write off a receivable, is threatened for fraud with a maximum imprisonment of four years. Keywords: crime, fraud, criminal liability.